2017
DOI: 10.1002/jcla.22300
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of absolute copy number variation of Glutathione S‐Transferase M1 gene by digital droplet PCR and association analysis in Tunisian Rheumatoid Arthritis population

Abstract: This study highlights the powerful accuracy of ddPCR for the quantification of CNVs and suggests that the variation in the CN of GSTM1 is associated with anti-CCP positivity in RA. However, it does not indicate a specific role in the susceptibility to the disease in our Tunisian sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Rheumatoid arthritis (RA) is characterized by a massive tissue infiltration of inflammatory cells and affects approximately 1% of the adult population worldwide. Clinically, it mainly causes the chronic inflammation of synovial joints, which will result in the progressive destruction of the cartilage and bone ( Achour et al, 2018 ). Many lines of data have implied the association of RA with genetic variations including SNPs and CNVs of several immune-related genes ( McKinney et al, 2008 ; Graf et al, 2012 ; Olsson et al, 2012 ).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Rheumatoid arthritis (RA) is characterized by a massive tissue infiltration of inflammatory cells and affects approximately 1% of the adult population worldwide. Clinically, it mainly causes the chronic inflammation of synovial joints, which will result in the progressive destruction of the cartilage and bone ( Achour et al, 2018 ). Many lines of data have implied the association of RA with genetic variations including SNPs and CNVs of several immune-related genes ( McKinney et al, 2008 ; Graf et al, 2012 ; Olsson et al, 2012 ).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…In 2011, a Swedish study found that more than one copy of glutathione S-transferase M1 ( GSTM1 ), a member of the GST family, seems to be a risk factor for autoantibody-positive RA in non-smoking females of age older than 60 years, and GSTM1 acts as a protective factor in ACPA-negative smoking men, suggesting that the copy number of the GSTM1 gene is correlated with the development and severity of RA ( Lundström et al, 2011 ). In 2016, it was also found that GSTM1 is deleted in Tunisian anti-cyclic citrullinated peptide (anti-CCP)-positive RA patients, although a genetic association of GSTM1 CNV with predisposition to RA was not detected ( Achour et al, 2018 ). The above data indicate that GSTM1 CNVs do not influence the susceptibility to RA, but may have an effect on its severity because deletion of GSTM1 could increase the risk of anti-CCP-positive RA.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%